(1R,2S,5R)-5-Methyl-2-[2-(4-nitrophenyl)propan-2-yl]cyclohexyl 2-(4-methoxyphenyl)-2,5-dihydro-1H-pyrrole-1-carboxylate: crystal structure and Hirshfeld analysis - Zukerman-Schpector, Julio; Soto-Monsalve, Monica; De Almeida Santos, Regina H.; Machado, Angelo H. L.; Correia, Carlos Roque D.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
In the title compound, C28H34N2O5, the adjacent ester and nitrobenzene substituents are connected via an intramolecular methylene-C—H. ...(nitrobenzene) interaction and the molecule approximates to a U-shape. The dihydropyrrole ring (r.m.s. deviation = 0.003 A ˚ ) is almost co-planar with the carboxylate residue [Cm—N—C1—Oc (m = methine, c = carboxyl) torsion angle = 1.8 (4).] but is orthogonal to the 4-methoxybenzene ring [dihedral angle = 84.34 (17).]. In the crystal, methylene-C—H. ...O(carbonyl) interactions lead to linear supramolecular chains along the b-axis direction, which pack without directional interactions between them. The analysis of the calculated Hirshfeld surface points to the importance of weak interatomic H. . .H, O. . .H/H. . .O and C. . .H/H. . .C contacts in the crystal.